Global statistics on addictive behaviours: 2014 status report - Gowing, L.; Ali, R.; Allsop, Steve; Marsden, J.; Turf, E.; West, R.; Witton, J. (Blackwell Publishing Ltd, 2015)
Background and aims: Addictive behaviours are among the greatest scourges on humankind. It is important to estimate the extent of the problem globally and in different geographical regions. Such estimates are available, but there is a need to collate and evaluate these to arrive at the best available synthetic figures. Addiction has commissioned this paper as the first of a series attempting to do this. Methods: Online sources of global, regional and national information on prevalence and major harms relating to alcohol use, tobacco use, unsanctioned psychoactive drug use and gambling were identified through expert review and assessed. The primary data sources located were the websites of the World Health Organization (WHO), the United Nations Office on Drugs and Crime (UNODC) and the Alberta Gambling Research Institute. Summary statistics were compared with recent publications on the global epidemiology of addictive behaviours. Results: An estimated 4.9% of the world's adult population (240million people) suffer from alcohol use disorder (7.8% of men and 1.5% of women), with alcohol causing an estimated 257 disability-adjusted life years lost per 100000 population. An estimated 22.5% of adults in the world (1billion people) smoke tobacco products (32.0% of men and 7.0% of women). It is estimated that 11% of deaths in males and 6% of deaths in females each year are due to tobacco. Of 'unsanctioned psychoactive drugs', cannabis is the most prevalent at 3.5% globally, with each of the others at <1%; 0.3% of the world's adult population (15million people) inject drugs. Use of unsanctioned psychoactive drugs accounts for an estimated 83 disability-adjusted life years lost per 100000 population. Global estimates of problem gambling are not possible, but in countries where it has been assessed the prevalence is estimated at 1.5%. Conclusions: Tobacco and alcohol use are by far the most prevalent addictive behaviours and cause the large majority of the harm. However, the quality of data on prevalence and addiction-related harms is mostly low, and comparisons between countries and regions must be viewed with caution. There is an urgent need to review the quality of data on which global estimates are made and coordinate efforts to arrive at a more consistent approach.